Anionic ring‐opening polymerization of a five‐membered cyclic carbonate having a glucopyranoside structure. Issue 7 (9th January 2013) - Azechi, Motohisa; Matsumoto, Kozo; Endo, Takeshi
Abstract Anionic ring‐opening polymerizations of methyl 4, 6‐O‐benzylidene‐2, 3‐O‐carbonyl‐α‐D‐glucopyranoside (MBCG) were investigated using various anionic polymerization initiators. Polymerizations of the cyclic carbonate readily proceeded by using highly active initiators such as n‐butyllithium, lithium tert‐butoxide, sodium tert‐butoxide, potassium tert‐butoxide, and 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene, whereas it did not proceed by using N, N‐dimethyl‐4‐aminopyridine and pyridine as initiators. In a polymerization of MBCG (1.0 M), 99% of MBCG was converted within 30 s to give the corresponding polymer with number‐averaged molecular weight (Mn) of 16, 000. However, the Mn of the polymer decreased to 7500 when the polymerization time was prolonged to 24 h. It is because a backbiting reaction might occur under the polymerization conditions. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013